Lenalidomide for the treatment of relapsed and refractory multiple myeloma - van de Donk NW; Görgün G; Groen RW; Jakubikova J; Mitsiades CS; Hideshima T; Laubach J; Nijhof IS; Raymakers RA; Lokhorst HM; Richardson PG; Anderson KC (Cancer Management and Research, 2012)
Niels WCJ van de Donk,1,2 Güllü Görgün,1 Richard WJ Groen,1,3 Jana Jakubikova,1 Constantine S Mitsiades,1 Teru Hideshima,1 Jacob Laubach,1 Inger S Nijhof,2 Reinier A Raymakers,2 Henk M Lokhorst,2 Paul G Richardson,1 Kenneth C Anderson11Department of Medical Oncology, Dana-Farber Cancer Institute, Harvard Medical School, Boston, MA, USA; 2Department of Hematology, 3Department of Cell Biology, University Medical Center Utrecht, Utrecht, The NetherlandsAbstract: Lenalidomide is an amino-substituted derivative of thalidomide with direct antiproliferative and cytotoxic effects on the myeloma tumor cell, as well as antiangiogenic activity and immunomodulatory effects. Together with the introduction of bortezomib and thalidomide, lenalidomide has significantly improved the survival of patients with relapsed and refractory myeloma. The most common adverse events associated with lenalidomide include fatigue, skin rash, thrombocytopenia, and neutropenia. In addition, when lenalidomide is combined with dexamethasone or other conventional cytotoxic agents, there is an increase in the incidence of venous thromboembolic events. There is now evidence that continued treatment with lenalidomide has a significant impact on survival by improving the depth and duration of response. This highlights the value of adverse event management and appropriate dose adjustments to prevent toxicity, and of allowing continued treatment until disease progression. In this review, we will discuss the different lenalidomide-based treatment regimens for patients with relapsed/refractory myeloma. This is accompanied by recommendations of how to manage and prevent adverse events associated with lenalidomide-based therapy.Keywords: lenalidomide, multiple myeloma, immunomodulatory drugs, relapse treatment, refractory disease